The role of cooperation agreements in the internationalization of Spanish winery and olive oil family firms. Issue 4 (28th August 2019) - Sanchez-Famoso, Valeriano; Cano-Rubio, Myriam; Fuentes-Lombardo, Guadalupe
Abstract : Purpose: This study aims to identify the mediating role of cooperation agreements in the relationship between family involvement in international firms and their level of international commitment. Design/methodology/approach: The study focuses on Spanish international wine and olive oil companies that have varying levels of family involvement. The final sample consists of 263 companies. SmartPLS was used to perform the analysis. Findings: A higher level of family involvement in business implies greater difficulties with cooperation agreements. Additionally, family involvement is negatively associated with the firm's level of international commitment, and the perceived difficulties of cooperation agreements mediate this relationship. Practical implications: This study is of interest to business managers with different levels of family involvement. The study clarifies their perceptions of cooperation agreements and international business commitment. Managers of firms with a high level of family involvement should emphasize the multiple benefits of cooperation agreements for international strategy performance rather than the drawbacks of cooperation. Additionally, through cooperation, companies can learn about destination markets, which may help them to focus their resources effectively in those markets. Originality/value: This study contributes to the literature on the internationalization strategies of family businesses. This study is the first to address the mediating role of cooperation agreements in the relationship between family involvement and international commitment.